Performance, carcass and meat characteristics of two cattle categories finished on pasture during the dry season with supplementation in different forage allowance - Aranha, A. S. [UNESP]; Andrighetto, C. [UNESP]; Lupatini, G. C. [UNESP]; Mateus, G. P.; Ducatti, C. [UNESP]; Roca, R. O. [UNESP]; Martins, M. B. [UNESP]; Santos, J. A. A.; Luz, P. A. C. [UNESP]; Utsunomiya, A. T. H. [UNESP]; Athayde, N. B. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2018)
The objective this paper was to evaluate the effect of two categories of beef finished in pasture with supplementation with two herbage allowance on performance, carcass and meat characteristics. Thirty-six Guzera cattle were used, 18 steers and 18 heifers with an initial age of 20 months. There was significant difference in daily weight gain for animal category and the herbage allowance, which were higher in males and animals submitted to high herbage allowance. Steers showed higher final weight, carcass weight and forequarter yield compared with the heifers, although the hindquarter yield was higher in the heifers, however the herbage allowance did not influence these characteristics. There were not statistical differences for carcass yield, ribeye area, backfat thickness and marbling score for the animal categories and herbage allowance. The meat chemical composition of the steers did not differ of the heifers, however, the animals submitted to high herbage allowance was increase in ether extract and pH, decrease in protein percentage. It was concluded that the animal category and the herbage allowance changed the animal performance, improving performance in males and cattle submitted to high herbage allowance.
Keywords: animal supplementation; meat quality; weight gain